MODERN ISLAMIC POETRY IN ACEH: T.M. Daud Gade's Syair Rabbani Wahid in the Perspective of Islamic Educational Psychology - Alwi, Said; Iqbal, Muhammad; Safitri, Maya (MIQOT: Jurnal Ilmu-ilmu Keislaman, 2023)
Abstract: Due to restrictions in developing and expressing the spiritual potential through the stylistic components in the poetry, Rabbani Wahid's poetry has not been studied adequately. The objective of this study is to provide an explanation for the poetry of Rabbani Wahid's, including the linguistic style, suggestive power, imagery, and emotions. The explanation for these elements involves a psychological perspective. The poetry collection Book of Rabbani Wahid, which has 11 sub-poems designated D1 to D11, provided empirical data for the study. The investigation starts by choosing a poem and utilizing literary analysis to examine its stylistic components. Applying tools for descriptive analysis is the next stage. The research's findings reveal that poetry's suggestive power is crucial because it may shape the reader's emotions, ideas, and behavior by using suitable words and language. The use of imagery, figurative language, and appropriate word placement can deepen the reader's understanding of the poetry's content. In order to elicit aesthetic and emotional responses from readers or listeners, Rabbani Wahid's poetry employs a variety of images, linguistic idioms, and phrases with great suggestive power. The poetry also conveys significant spiritual lessons about the value of doing good deeds, love for Allah and the Prophet Muhammad, humility, and simplicity. Litotes, repetition, personification, and simile are figurative language techniques that are employed to enhance the language style and express significant spiritual themes about humbling oneself and practicing simplicity in worship.Keywords: spiritual psychology, Rabbani Wahid, poetry, stylistic approach